Separate collection of plastic waste, better than technical sorting from municipal solid waste?. Issue 2 (February 2017) - Feil, Alexander; Pretz, Thomas; Jansen, Michael; Thoden van Velzen, Eggo U
The politically preferred solution to fulfil legal recycling demands is often implementing separate collection systems. However, experience shows their limitations, particularly in urban centres with a high population density. In response to the European Union landfill directive, mechanical biological waste treatment plants have been installed all over Europe. This technology makes it possible to retrieve plastic waste from municipal solid waste. Operators of mechanical biological waste treatment plants, both in Germany and the Netherlands, have started to change their mechanical separation processes to additionally produce plastic pre-concentrates. Results from mechanical biological waste treatment and separate collection of post-consumer packaging waste will be presented and compared. They prove that both the yield and the quality of plastic waste provided as feedstock for the production of secondary plastic raw material are largely comparable. An economic assessment shows which conditions for a technical sorting plant are economically attractive in comparison to separate collection systems. It is, however, unlikely that plastic recycling will ever reach cost neutrality.